(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2018)
This article comprehensively analyses nomination as applied in the banking, takaful and contribution system, and its implications from the perspective of Islamic law. The study employs the qualitative approach of content analysis. The findings of the study are that the introduction of nomination in the Islamic financial system gives the depositors, takaful participants and contributors options when it comes to the administration and distribution of property after death. In addition, nomination is also a convenient mechanism and speeds up the payment of savings, takaful benefits and contributions after the death of depositors, takaful participants or contributors. This study also suggests steps that can be taken to protect the interests of the recipients entitled to the property of the deceased. Keywords: nomination, implications, banking, takaful contribution